A dynamic Biologically-Active Layer for numerical studies of the sea ice ecosystem. - Tedesco, L.; Vichi, M.; Haapala, J.; Stipa, T. (Ocean Modelling, 2010)
This work introduces a novel approach for the modelling and coupling of sea ice biology to sea ice physics. The central concept of the coupling is the definition of the Biologically Active Layer, which is the time-varying fraction of sea ice that is connected to the ocean via brine pockets and channels, and acts as a rich habitat for many microorganisms. A simple but comprehensive physical model of the sea ice thermohalodynamics is coupled to a novel sea ice microalgal model of growth in the framework of the Biogeochemical Flux Model. The physical model provides the key physical properties of the Biologically Active Layer and the biological model simulates the physiological and ecological response of the algal community to the physical environment. Numerical simulations of chl-a were compared with observations at two different ice stations, in the Baltic and off the coast of Greenland, showing that this new coupling structure is sufficiently generic to represent well the temporal and spatial distribution of sea ice algae during the whole ice season at both sites. This model implementation and coupling structure is viable as a new component of General Circulation Models, allowing for estimates of the role and importance of sea ice biology in the local and global carbon cycle. Italian FISR project VECTOR Published 89-104 3.7. Dinamica del clima e dell'oceano JCR Journal restricted